Skates and rays (Elasmobranchii, Batomorphii) from the Eocene La Meseta and Submeseta formations, Seymour Island, Antarctica - Engelbrecht, Andrea (2019)
Eocene deposits of the famous La Meseta Formation of Seymour Island, Antarctic Peninsula, yielded the most diverse Paleogene fossil elasmobranch association of the Southern Hemisphere. In this assemblage, sharks clearly dominate the fauna, whereas batoids are very rare components. Herein, we describe two new taxa of cold water tolerant skates, Marambioraja leiostemma gen. et sp. nov., and Mesetaraja maleficapelli gen. et sp. nov., two new species of the genus Raja, Raja amphitrita sp. nov. and Raja manitaria sp. nov., as well as remains of warm water adapted myliobatiforms. It is, however, not possible to unambiguously assign these remains either to Myliobatidae or Rhinopteridae, or to any specific genus. Previously reported remains of Raja/Bathyraja sp. are assigned to the new described species Raja manitaria sp. nov. The biogeographic distribution of extant and extinct rays and skates clearly shows that both groups are more widely distributed today than in the past, and additionally seem to have been more diverse in the Northern than the Southern Hemisphere. The occurrence, albeit rare of isolated teeth of skates (Rajidae) and rays (Myliobatidae) in the La Meseta Formation representes a minimum age constraint for their first appearance in the Southern Ocean.